Analisis Revisit Intention Pendakian di Masa Pandemi Covid-19 - Oce Ridwanudin; Fahry Ahmad (Tourism Scientific Journal, 2021)
The development of the tourism industry in Indonesia until early 2020 has contributed quite a lot to the country's foreign exchange, but since the Covid 19 pandemic this has had a negative impact on the tourism industry so that it has experienced a significant decline. With the Covid-19 pandemic, it has resulted in a decrease in the number of tourists in various tourist destinations, one of which is a special interest tourist destination, namely the mountains. Among the many mountains that exist, one of the mountains affected by the Covid-19 pandemic is Mount Gede Pangrango and Mount Semeru. The Covid-19 pandemic caused the closure of the climbing routes of Mount Gede Pangrango and Mount Semeru. The purpose of this study is to obtain findings regarding the motivation and experience of climbing in creating tourists who have a revisit intention to increase visits to Mount Gede Pangrango and Mount Semeru. The research method used is a qualitative method. The sample used by tourists who had climbed Mount Gede Pangrango and Mount Semeru during the Covid-19 pandemic.